QUANTITATIVE GENETIC IMPROVEMENT IN AUTOGAMOUS PLANTS: APPLICATION OF RECURRENT SELECTION - Costa, Aristeu Antonio Lourenco; de Brito, Raimundo Filho Freire; de Araújo, Nicolas Oliveira; Freire, Ana Izabella; de Souza, Filipe Bittencourt Machado (Seven Editora, 2024)
The text addresses genetic improvement in plants that reproduce by self-fertilization, focusing on characteristics such as productivity, resistance to pests and diseases, and fruit quality. Recurrent selection is highlighted as a strategy to increase genetic variability and improve the effectiveness of selection over consecutive cycles. In the study described, two soybean cultivars adapted to the target region are artificially crossed in a greenhouse, with the objective of creating a segregating population. The breeding method used is SSD (Single Seed Descent), which facilitates the obtaining of homozygous lines by reducing the time required for this and requires less space, and the populations are conducted in environments such as greenhouses. DOI:https://doi.org/10.56238/sevened2024.032-001